2017
DOI: 10.5740/jaoacint.17-0122
|View full text |Cite
|
Sign up to set email alerts
|

A Multivariate Analysis of the Composition and Properties of Extra Virgin Olive Oils Produced from Different Cultivars Grown in Iran

Abstract: The present study investigated variations in extra virgin olive oils in relation to fatty acid (FA) composition and the characteristics of 10 olive cultivars. The findings demonstrated that their oil yield properties, including refractive index, acid value, peroxide value, saponification value, iodine value, and composition, were significantly different. Moreover, based on GC-MS analysis, the presence of oleic acid [C18:1(9)] was identified as one of the major components. The highest amount of 18:1(9) was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The iodine index is a measure of the unsaturation of fats and oils and consequentially the susceptibility to oxidation [ 29 ]. The obtained iodine index (76.7 I 2 /100 −1 g) is close to values found in analyses of 10 oils of different cultivars of olive ( Olea europaea L.), between 80 and 89 I 2 /100 −1 g [ 30 ]. Its counterpart, the oil of the fruit of Byrsonima cydoniifolia A.…”
Section: Resultssupporting
confidence: 81%
“…The iodine index is a measure of the unsaturation of fats and oils and consequentially the susceptibility to oxidation [ 29 ]. The obtained iodine index (76.7 I 2 /100 −1 g) is close to values found in analyses of 10 oils of different cultivars of olive ( Olea europaea L.), between 80 and 89 I 2 /100 −1 g [ 30 ]. Its counterpart, the oil of the fruit of Byrsonima cydoniifolia A.…”
Section: Resultssupporting
confidence: 81%
“…A higher acid value and peroxide value of an oil is an indicator of the generation of impurities in the oil. The presence of impurities in the oil increases its relative density [24], refractive index [25] and also affects its absorbance at 270 nm (A 270 ) [26] because these impurities increase the atomic numbers of the constituent atoms in the oil. The results provided in the Table 1 revealed that the values of the relative density, refractive index, and A 270 of the sample oils and the reference oil complied with their standard values.…”
Section: Relative Density Refractive Index and Absorbancementioning
confidence: 99%
“…Ultrasonic-assisted extraction, ionic liquid extraction, microwave-assisted extraction and supercritical fluid extraction require relatively less solvent, and they can separate phenolic compounds efficiently with good reproducibility. The characteristics of low extraction temperature and time-saving are also more suitable for industrial production Morgan, 2013;Shirzad et al, 2017).…”
Section: Introductionmentioning
confidence: 99%